Human and Minority Rights Protection by Multiple Diversity Governance (Taylor & Francis, 2023)
Human and Minority Rights Protection by Multiple Diversity Governance provides a comprehensive overview and critical analysis of minority protection through national constitutional law and international law in Europe. Using a critical theoretical and methodological approach, this textbook: provides a historical analysis of state formation and nation building in Europe with context of religious wars and political revolutions, including the (re-)conceptualisation of basic concepts and terms such as territoriality, sovereignty, state, nation and citizenship;